Violence against women as a form of sex discrimination and as a result of gender stereotypes - Michailovič, Ilona (Information & Media, 2018)
There is a reoccurring relationship between the functioning and dissemination of gender stereotypes, violence against women and discrimination against women. Negative stereotypes of women still do exist and are still firmly established. In this article, we demonstrate the consequences of the existence of such stereotypes, and we analyze the decisions of the United Nations Committee on the Elimination of Discrimination against Women regarding sexual violence against women.The article addresses a range of issues that expressly substantiate a need for effective measures in respect of violence against women. The process of positive change of social views on the traditional role of women and men is certainly a long process, and it cannot be done without the inspiration and activity of both the individual states and international organizations. The contributions of numerous international institutions in this area have been demonstrating increasingly clearly that any state is fundamentally obliged to confront violence both in the public domain and private environments, and that it must ensure the safety, protection and assistance for victims of violence.